THE USE OF EDUCATIONAL TECHNOLOGIES IN TEACHING ENGLISH (Modern education and development, 2025)
the use of educational technology in teaching English has become an important aspect of the educational process today. Educational technology allows teachers and students to conduct classes more interestingly and efficiently. In this article, we will talk in detail about the importance of educational technologies in teaching English, their types, advantages and effects.